PROBLEMS AND DEVELOPMENT PROSPECTS OF THE RA HIGHER EDUCATION SYSTEM (Education in the 21st Century, 2023)
The sphere of higher professional education being the basis of the intellectual potential of the society and the development of the economy is of strategic importance in the process of sustainable development of the states.The present article portrays the problems of the sphere of higher professional education of the Republic of Armenia, based on the analysis of the legislation regulating the sphere. We have also studied the changes (outlining the development prospects and directions of the sphere) proposed by the draft law, which will significantly change the sphere of higher education, from structure to management. From the above study, it becomes obvious that all the ongoing and planned changes in the sphere of higher professional education in the Republic of Armenia are aimed at full integration into the European Higher Education Area.